First expierence of hypoxyhyperoxytherapy - O. К. Gogayeva; V. V. Lazoryshinets; L. S. Dzakhoieva; О. М. Pisarev (Ukrainian Journal of Cardiovascular Surgery, 2016)
The article presents first experience of using normobaric hypoxyhyperoxytherapy in National Amosov’s Institute of cardiovascular surgery for patients with hypertension and stable coronary heart disease.Interval hypoxytherapy conducted on medical diagnostic device with innovative SRT technology (self-regulated treatment) – ReOxy.